2012
DOI: 10.1161/circep.111.969782
|View full text |Cite
|
Sign up to set email alerts
|

MK-0448, a Specific Kv1.5 Inhibitor

Abstract: Background-We evaluated the viability of I Kur as a target for maintenance of sinus rhythm in patients with a history of atrial fibrillation through the testing of MK-0448, a novel I Kur inhibitor. Methods and Results-In vitro MK-0448 studies demonstrated strong inhibition of I Kur with minimal off-target activity. In vivo MK-0448 studies in normal anesthetized dogs demonstrated significant prolongation of the atrial refractory period compared with vehicle controls without affecting the ventricular refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
(37 reference statements)
3
25
0
Order By: Relevance
“…One compound, MK-0448, that is selective for Kv1.5 over other cardiac ion channels, showed efficacy in multiple preclinical models of AF and was examined in an invasive electrophysiological study in healthy volunteers. 47 In this study, MK-0448 did not prolong the atrial refractory period. Follow-up studies in anesthetized dogs attributed the lack of effect to the high vagal tone in young, healthy subjects such as those participating in the study.…”
Section: Kv15mentioning
confidence: 44%
See 1 more Smart Citation
“…One compound, MK-0448, that is selective for Kv1.5 over other cardiac ion channels, showed efficacy in multiple preclinical models of AF and was examined in an invasive electrophysiological study in healthy volunteers. 47 In this study, MK-0448 did not prolong the atrial refractory period. Follow-up studies in anesthetized dogs attributed the lack of effect to the high vagal tone in young, healthy subjects such as those participating in the study.…”
Section: Kv15mentioning
confidence: 44%
“…Follow-up studies in anesthetized dogs attributed the lack of effect to the high vagal tone in young, healthy subjects such as those participating in the study. 47 Although vagal tone may be reduced in the patient population, the greater risk for episodes of AF associated with vagal stimulation does not bode well for this mechanism, and clinical development of MK-0448 was discontinued. However, a recent study with MK-0448 in human atrial tissue from sinus rhythm controls and from permanent AF patients showed that MK-0448 delayed the effective refractory period in atrial tissue from AF patients and not from control subjects.…”
Section: Kv15mentioning
confidence: 99%
“…Furthermore, the mechanism of I Kur in dog atrium is different from that in humans, and the magnitude is often very small (34). MK-0448 failed to prolong AERP in healthy human subjects using relatively slow stimulation cycle lengths of 400 and 600 ms at which I Kr recruitment balances I Kur block (35). I Kur block ratedependence, as described in this study, along with speciesand remodeling-related differences, likely account for these conflicting results.…”
Section: Relevance For Antiarrhythmic Drug Developmentmentioning
confidence: 64%
“…It is worth keeping in mind that chronic AF in humans might reduce K V 1.5 expression and thereby I Kur density (78,439). Also it should be mentioned that the importance of I Kur in humans seems to be less pronounced than suggested from preclinical animal models (336). In addition, I Kur density is diminished at high atrial heart rates as seen in AF (122).…”
Section: Kur Blockersmentioning
confidence: 98%